Jejunal mucosal morphology in healthy north Indian subjects. - Bennett, M K (1985)
Morphometric measurements have been performed on small intestinal biopsy specimens obtained from 18 healthy adult Indian volunteers. The measurements were made using a computer aided measuring system, and results were similar to those previously reported for an adult Caucasian population.